Effect of Using Smart Mobile Device on Child Prosocial and Difficult Behaviors in School Age; Parents’ Perception - Samar Salah Eldin Mohamed Diab (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The time that children spend using digital devices is increasing rapidly with the developmentof new portable and instantly accessible technology. Mobile devices are embedded in and dominate the dailylives of young children. Research Aims: assess the effect of using smart mobile device on child Prosocialand difficult behaviors in school age. Methodology: A cross sectional research design was utilized at August2019 - January 2020. Convenience sample include the 400 school children. An online survey by usingGoogle form, which contains three parts (characteristics of parents, children and Strengths and DifficultiesQuestionnaire). Results: revealed that47.2% and 47.7% of studied children had abnormal emotionalsymptoms and conduct problems. In addition (34.5%) of studied children was normal related peer problemsdomain. Also, (51.2%) of them was abnormal related hyperactivity. While, (30%) of studied children hadnormal Prosocial behavior. Conclusions: the current study concluded that about half of studied children hadabnormal Prosocial and difficult behaviors and less than one quarter of them had borderline Prosocial anddifficult behaviors. While, less than one third of them had normal Prosocial and difficult behaviors.